PSYCHOLOGICAL DIFFICULTIES IN MARITAL RELATIONSHIPS RELATED TO THE REALIZATION OF THE REPRODUCTIVE FUNCTION (Psychology Travelogs, 2023)
The article provides a theoretical study of the psychological difficulties faced by marital partners when fulfilling the reproductive function. The reasons for the emergence of factors influencing the decision to become parents are highlighted: motivation for parenthood, stress, emotional-psychological readiness, partner's behavior model, partner's career realization, social pressure, issues with sexual life, conflicts between marital partners.Identified are signs indicating discrepancies in views and plans, disagreements regarding various household matters, economic-financial issues, and the distribution of responsibilities between marital partners. It has been established that discrepancies and disagreements in relationships can have serious consequences, eventually leading to communication barriers, decreased intimacy, and even the dissolution of the marital union. It is noted that the desire of a couple to fulfill the reproductive function can lead to conflicts due to differing levels of psychological readiness of marital partners, particularly concerning motivations for childbirth and the need for children. Reproductive motivation reflects the mental states of each spouse and can differently prompt them to have children. Marital partners should possess a solid understanding of parenthood/motherhood, comprehend potential psychological difficulties associated with reproductive function realization, and implement effective behavior models for this stage.The article outlines prospects for further development of effective psychological approaches and interventions to support marital partners facing psychological challenges in marital relationships linked to reproductive function realization. The aim is to overcome the causes of negative factors provoking their emergence.
Keywords: reproductive function; psychological difficulties; discrepancies; disagreements; marital relationships